2016
DOI: 10.1136/neurintsurg-2016-012716
|View full text |Cite
|
Sign up to set email alerts
|

A standardized neurointerventional thrombectomy protocol leads to faster recanalization times

Abstract: Background and purpose Intra-arterial therapy (IAT) is most effective when performed rapidly after ischemic stroke onset. However, there are limited performance benchmarks in IAT and there is a scarcity of information on how to structure an effective IAT protocol and its impact on time to treatment. The objective of our study was to detail a standardized IAT protocol, and to assess its influence on time to treatment in ischemic stroke. Methods This was a retrospective observational study over 4 years at a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
(40 reference statements)
0
38
0
Order By: Relevance
“…However, only 13% and 4% of the randomized patients were treated within the ‘ideal’ SNIS 2015 intervals of ≤60 min for door to groin time and ≤30 min for imaging to groin time. 13 Even with a streamlined process, Frei et al 14 recently reported a median door to groin time of 71 min for direct admission patients undergoing triage with MDCT.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 13% and 4% of the randomized patients were treated within the ‘ideal’ SNIS 2015 intervals of ≤60 min for door to groin time and ≤30 min for imaging to groin time. 13 Even with a streamlined process, Frei et al 14 recently reported a median door to groin time of 71 min for direct admission patients undergoing triage with MDCT.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data show a further significant reduction of time from admission to reperfusion compared to other studies proposing a streamlined patient management 11 . Patients not meeting the criteria required for the one stop management approach, i.e.…”
Section: Introductionmentioning
confidence: 69%
“… 39 In parallel, the nurse and NI technologist prepare the angiography suite for the upcoming thrombectomy procedure. 40 This team-based approach resulted in a marked reduction in the treatment time and increase in the number of patients successfully treated in the American Heart Association's Best Practice Strategies. 41 …”
Section: In-hospital Angiography Suite Phasementioning
confidence: 99%
“…A standardized stroke kit, so called BRISK (brisk recanalization ischemic stroke kit), was used in a previous report for time-saving process improvement. 40 All NI team members should be well-acquainted with the exact location of the prepared EVT kit and standardized stroke kit in the angiography suite for rapid deployment. Similarly, all members should be familiar with tasks for thrombectomy procedure so that critical functions are duplicated and replaced.…”
Section: In-hospital Angiography Suite Phasementioning
confidence: 99%